Psychology of Sustainability: Education for Sustainable Development in India - Atasi Mohanty; Ashraf Alam; Aashish Mohanty (Scientia Publica Media, 2025)
The intersection of psychology and sustainability within the domain of education represents a critical nexus for understanding and addressing pressing environmental challenges facing humanity. The paper embarks on a comprehensive journey through the interplay between psychology and sustainability in education, illuminating key theoretical frameworks, empirical insights, and practical implications for fostering sustainable mindsets and behaviors among individuals and communities. Central to the inquiry is the recognition of the urgent need for transformative approaches in education to mitigate climate change, biodiversity loss, and resource depletion. Through an interdisciplinary lens, the paper navigates the complex terrain of human cognition, emotion, and decision-making processes underlying attitudes and behaviors towards the environment. Psychological theories such as cognitive dissonance, environmental identity, and behavioral economics serve as foundational pillars for understanding the complexities of sustainable behavior and the barriers hindering its adoption. Moreover, the paper elucidates the pivotal role of education in cultivating sustainable mindsets and behaviors, emphasizing the significance of Education for Sustainable Development (ESD) as a catalyst for transformative learning and societal change. From curriculum design to campus operations, Higher Education Institutes (HEIs) emerge as key actors in advancing sustainability goals and nurturing a culture of environmental stewardship. As agents of change, teachers wield considerable influence in shaping the attitudes and behaviors of future generations towards sustainability, highlighting the importance of innovative pedagogies, experiential learning, and transformative teaching practices. Through the integration of psychology, education, and environmental stewardship, we can pave the way towards a brighter tomorrow grounded in principles of sustainability, resilience, and social justice.